Factors Associated With Survival and Return to Function Following Synovial Infections in Horses - Crosby, Danielle E.; Labens, Raphael; Hughes, Kristopher J.; Nielsen, Sharon; Hilbert, Bryan J. (Frontiers in Veterinary Science, 2019)
Synovial infections (SI) are common in horses of all ages and can be associated with high rates of morbidity and mortality. Identifying factors influencing survival and return to function may be useful for management of affected individuals and determination of prognosis. The objectives of this study were to identify factors associated with survival and return to function of horses and foals with SI presented to an equine hospital. This study is a retrospective case series. Data were collected from medical records of all horses with SI that were presented to a single equine hospital between April 1st, 2008 and May 1st, 2017. Long–term follow up was obtained by a semi-structured telephone questionnaire of clinical outcomes and analysis of online race records. Univariate models were created using generalized linear and linear mixed models to assess factors associated with outcomes. Multivariable models were created using generalized linear and linear mixed models to determine factors significantly associated with outcomes. Of 186 horses presented with SI, 161/186 (86.6%) were treated and 145/161 (90.1%) survived to discharge. One hundred and twenty horses were included in the return to function analysis and 79 (65%) returned to function. Increasing number of days of treatment with systemic antimicrobials was associated with increased likelihood of survival at both the horse level (OR 1.15, 95%CI 1.04—1.27, P=0.025) and level of the individual synovial structure (OR 1.11, 95%CI 1.04—1.17, P=0.004). Horses treated with doxycycline were less likely to return to function (OR 0.39, 95%CI 0.19—0.8, P=0.031). The overall rate of survival of horses treated with SI is good. The likelihood of return to function is lower than for survival. The findings of this study can be used as a part of evidence–based decision–making when veterinarians are treating horses with SI.